2021
DOI: 10.1111/gove.12633
|View full text |Cite
|
Sign up to set email alerts
|

Messaging about corruption: The power of social norms

Abstract: While commonly deployed in anti‐corruption programs, corruption messaging has shown limited success. I argue that strategies focusing on injunctive norms (what most people approve of) have been underutilized and could be a feasible way of influencing perceptions in a desirable direction. In two studies fielded in Mexico, I first identify a substantial discrepancy between how individuals view the permissibility of corruption and their perceptions of other people's attitudes. In a follow‐up preregistered experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…A much smaller literature focuses on the impact that messages about corruption have on beliefs and behaviour about corruption and efforts to combat it. To date, six studies have directly assessed the influence of anti-corruption messaging on beliefs about corruption, anti-corruption, and to a more limited extent, "corrupt" behaviour (Agerberg, 2021;Cheeseman & Peiffer, 2020;Chong et al, 2015;Corbacho et al, 2016;Kobis et al, 2019;Peiffer, 2017Peiffer, , 2018. Unlike the literature on messaging and voting behaviour, the findings from these studies are more consistent, with most suggesting that messages about corruption and anti-corruption are at best an ineffective tool with which to fight corruption, or are at worst backfiring to some extent.…”
Section: Re S E Arch On Anti -Corrup Ti On Me Ssag Ingmentioning
confidence: 99%
See 2 more Smart Citations
“…A much smaller literature focuses on the impact that messages about corruption have on beliefs and behaviour about corruption and efforts to combat it. To date, six studies have directly assessed the influence of anti-corruption messaging on beliefs about corruption, anti-corruption, and to a more limited extent, "corrupt" behaviour (Agerberg, 2021;Cheeseman & Peiffer, 2020;Chong et al, 2015;Corbacho et al, 2016;Kobis et al, 2019;Peiffer, 2017Peiffer, , 2018. Unlike the literature on messaging and voting behaviour, the findings from these studies are more consistent, with most suggesting that messages about corruption and anti-corruption are at best an ineffective tool with which to fight corruption, or are at worst backfiring to some extent.…”
Section: Re S E Arch On Anti -Corrup Ti On Me Ssag Ingmentioning
confidence: 99%
“…Taken together, these studies suggest messaging is ineffectual, or worse, that it may backfire. The field study conducted by Agerberg (2021) in Mexico is the exception to this rule; he found that informing respondents about people's strong anti-corruption attitudes resulted in them being less willing to engage in bribery. Somewhat remarkably, however, none of these studies assesses whether anti-corruption messaging has an impact on the willingness to report corruption-which is a key objective of anti-corruption campaigns around the world.…”
Section: Re S E Arch On Anti -Corrup Ti On Me Ssag Ingmentioning
confidence: 99%
See 1 more Smart Citation
“…In all realms where individuals perceive that a given behavior can be deemed more or less acceptable by others, normative influences are likely to affect them. Prominent examples include gender relations (e.g., Felmlee, 1999), intergroup contact (e.g., Mähönen, Jasinskaja-Lahti, and Liebkind, 2011) or tolerance of corruption (e.g., Agerberg, 2022).…”
Section: Forthcoming In the Encyclopedia Of Political Sociology Edite...mentioning
confidence: 99%
“…The literature on public relations campaigns has so far offered one potential ray of hope. Messages that avoid telling the public how bad the situation is (descriptive norm) and instead emphasise how much the public disapproves of a particular kind of behaviour (injunctive norm)such as organised criminal activitymay encourage hope that the social bad can be tackled, and/or even a rejection of the social bad itself (Widner and Roggenbuck, 2000;Cialdini et al, 2006;Agerberg, 2022). By not highlighting the extent of the problem, injunctive norm messaging is thought to be better placed to reduce the risk of priming pessimistic beliefs, and at the same time promote the idea that the socially acceptable form of behaviour is to reject the social bad (Tankard and Paluck, 2016;Agerberg, 2022).…”
mentioning
confidence: 99%